A Microvascular‐Based Multifunctional and Reconfigurable Metamaterial (Adv. Mater. Technol. 11/2021). Issue 11 (5th November 2021) - Devi, Urmi; Pejman, Reza; Phillips, Zachary J.; Zhang, Pengfei; Soghrati, Soheil; Nakshatrala, Kalyana B.; Najafi, Ahmad R.; Schab, Kurt R.; Patrick, Jason F.
Abstract : Microvascular‐Based Metamaterial In article number 2100433, Jason F. Patrick and coworkers demonstrate a microvascular‐based multifunctional and reconfigurable metamaterial where various physical properties (i.e., electromagnetic signature and thermal profile) are dynamically modulated within a structural fiber‐reinforced composite via fluid exchange (i.e., liquid metal and water) within a bioinspired vasculature.